Understanding Customer Perception of Airline Service Quality and Brand Image: A Pathway to Loyalty and Repurchase Intentions - Astri Rumondang Banjarnahor; Juliater Simarmata; Rudi Max Damara Gugat; Otto Sugiharto Prakoso; Andre Yosafat (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates how customer perceptions of service quality and airline brand image affect customer loyalty and intentions to repurchase. By employing a systematic literature review (SLR) method in line with the PRISMA protocol, the research examines 50 articles indexed in Scopus that pertain to customer perceptions in the airline sector. The results indicate that favorable perceptions of service quality significantly impact brand image, thereby promoting customer loyalty and repurchase intentions. Mediating factors such as